Peranan Guru Pendidikan Agama Islam dalam Pembentukan Karakter Islami : Studi Kasus Siswa MTs. al Huriyah Rejoso Pasuruan - Syaifi, Mat (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
This research is motivated by a phenomenon of student delinquency which has recently become increasingly worrying, such as: brawls between students, promiscuity among teenagers, drug abuse and so on, from these problems teachers, especially Islamic religious education teachers, have a duty and role to improve behavior. Islamic students. The focus of the research in this case is knowing the role of Islamic Religious Education teachers in the formation of Islamic character, knowing the formation of character education by Islamic Religious Education teachers, knowing the supporting and inhibiting factors for Islamic Religious Education teachers in forming the character of class VII-A MTs students. al Huriyah Rejoso Pasuruan. This research was prepared based on field data using a qualitative approach. Data collected using observation, interviews and documentation. Meanwhile, for the analysis, the researcher used descriptive qualitative, namely in the form of a comprehensive description and description of the data collected about the actual situation. The results of this research indicate that Islamic religious education teachers play a role in shaping students' Islamic behavior. The role of teachers as educators in shaping students' Islamic behavior in class VII-A MTs students. al Huriyah Rejoso Pasuruan, namely by always guiding and developing students to behave Islamically on a daily basis.